ANALISIS MODEL RASCH UNTUK MENGUKUR KOMPETENSI PENGETAHUAN SISWA SMKN 1 KALIANGET PADA MATA PELAJARAN PERAWATAN SISTEM KELISTRIKAN SEPEDA MOTOR - Ngadi, Ngadi (Jurnal Pendidikan Vokasi Otomotif, 2023)
Vocational students are prepared to work in certain positions through a curriculum in which its learning materials consist of 30% theory and 70% skill. It makes their mindset more concerned with skill-based subjects, not motivated to study the material theoretically, and reluctant to take knowledge-based tests. Knowledge is an important aspect for understanding, reasoning, and leading to rational actions when practicing. There is a need for the appropriate measuring tool for diagnosing the knowledge of vocational students in mapping knowledge so that it can be used to provide improved learning services in vocational high schools. The Rasch model is a modern evaluation tool using probability responses to items in a distribution map, so that the characteristics of vocational students in answering questions can be evaluated, starting from the level of students' abilities, distribution maps of ability and difficulty items, as well as a map of the distribution of answers that reflects their honesty. The research was conducted at the Motorcycle Engineering and Business Skills Competency Program (TBSM) of SMKN 1 Kalianget on the subject of Electrical System Maintenance, on the theme of Ignition System Maintenance, with 49 respondents. The instrument was 30 items of a multiple-choice test which was developed according to the Minister of Education and Culture of the Republic of Indonesia Number 23 of 2017 and the second Level of the Qualification Certification Scheme on TBSM Competence from BNSP 2017. The test result shows that instruments have good quality, by fulfilling the elements of reliability, validity (MNSQ outfit and ZSTD outfit, DIF item, unidimensional test), separation, and item difficulty level. Students' knowledge ability is in the high category (44.9%), medium (44.94%), low as well as very low (only 8.16%). The results of Wright Map depict respondents' opportunity to answer correctly by 57.14%. Based on the Guttman matrix scalogram, the percentage of careless students is just 2.04%, but that of students guessed the answers correctly is 12.24%